Binder Chemistry Dependent Electrolyte Reduction in Potassium‐Ion Batteries: A Successive, Two‐Step Reduction Way. Issue 2 (22nd November 2022) - Zhou, Wang; He, Bingchen; Quan, Lijiao; Li, Ruhong; Chen, Yuqing; Fan, Changling; Chen, Shi; Xu, Chaohe; Fan, Xiulin; Xing, Lidan; Liu, Jilei
Abstract: Controlling electrode/electrolyte interfacial chemistry is critically important for improved K + storage, but the influences of binder chemistry on electrolyte decomposition and interfacial properties are still poorly understood. Herein, sodium carboxymethyl cellulose (CMC)‐based, and polyvinylidene fluoride (PVDF)‐based graphite electrodes are introduced as model systems to quantify the electrolyte decomposition, solid electrolyte interphase (SEI) formation, and the corresponding kinetic evolution transition. A noncatalytic electrolyte reduction path on the CMC‐based electrode and a catalytic reduction path on the PVDF‐based electrode are identified, in terms of the reduction overpotential and product selectivity. The electrolyte reduction and/or SEI formation are found to occur in a successive, two‐step manner, starting with the electrochemical reduction at a potential above 0.35 V where no potassiation has happened (step I), and followed by the thermodynamically accelerated electrolyte reduction at a potential below 0.35 V (step II). Kinetics analysis reveals the former is charge transfer‐controlled for both CMC and PVDF‐based electrodes, and the latter involves a kinetic transition to SEI resistance controlled for the PVDF system, while it is charge transfer‐controlled for the CMC system. All these examples, highlight that binder chemistry plays a dominant role in the electrolyte decomposition and electrode/electrolyte interfacial properties, and promote a better fundamental understanding of electrolyte reduction. Abstract : Successful elucidation of binder chemistry‐dependent, successive, two‐step electrolyte reductions, that is, starting with the electrochemical reduction, followed by the thermodynamically accelerated electrolyte reduction, promotes fundamental understanding of electrolyte reduction and electrode/electrolyte interfacial properties, which enables rational design of high‐performance potassium‐ion batteries.